Ernesto Laclau : post-marxism, populism, and critique - Laclau, Ernesto, 1935-2014.; Howarth, David R. (2015)
"Ernesto Laclau has blazed a unique trail in political theory and philosophy since the early 1970s. In so doing, he has articulated a range of philosophical and theoretical currents into a coherent alternative to mainstream models and practices of conducting social and political science"--
Introduction : post-marxism, populism and critique / David Howarth -- Discourse (1993) --Dislocation and Capitalism and Social Imaginary and Democratic Revolution (1990) -- Why do Empty Signifiers Matter to Politics? (1994) -- The Death and Resurrection of the Theory of Ideology (1996) -- Ideology and Post-Marxism (2007) -- Towards a Theory of Populism (1977) -- Populism : What's in a Name? (1989) -- Why Constructing a People Is the Main Task of Radical Politics (2006) -- "The Time is Out of Joint" (1995) -- Can Immanence Explain Social Struggles? (2003) -- On "Real" and "Absolute" Enemies (2005) -- Bare Life or Social Indeterminacy? (2005) -- Community and its Paradoxes : Richard Rorty's "Liberal Utopia" (1991) -- An Interview with Ernesto Laclau : interview questions from David Howarth.
Includes bibliographical references and index.
Keywords: Populism -- Philosophy; Socialism -- Philosophy; POLITICAL SCIENCE / General; POLITICAL SCIENCE / Civics & Citizenship; POLITICAL SCIENCE / Political Process / Political Parties